An Act to establish the Anti-Corruption Agency, to vest powers on officers of the Agency and to make provisions connected therewith. - Rohimi Shapiee (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
An Act to establish the Anti-Corruption Agency,  to vest powers on officers of the Agency and to make provisions connected therewith.